Transformasi Zakat: Digitalisasi dan Inovasi dalam Pengelolaan Zakat di Era Modern - Ratu Aisyah; Melani Putri; Abdee putra wiguna; Muhammad Zaki; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Zakat, as one of the pillars of Islam, has great potential in supporting sustainable economic development, especially in the modern era which is characterized by technological advances and rapid social change. This research aims to explore the role of zakat in supporting sustainable economic development in the modern era, with a focus on its impact on reducing poverty and increasing community welfare. In this context a qualitative approach is used to analyze data from various sources, including case studies of zakat institutions, interviews with managers. zakat, and a review of related literature. Zakat not only functions as a tool for wealth redistribution, but can also be used to support entrepreneurship and small business development. Research results show that zakat has significant potential in improving community welfare, especially through funding entrepreneurship and small businesses. Digitalization of the zakat process has accelerated collection and distribution, increased transparency and accountability, and expanded the reach of zakat recipients. Zakat can be a vital instrument in achieving sustainable development goals. With collaboration between zakat institutions, the government and the private sector, zakat can have a greater positive impact in creating a just and sustainable society.